Effect of Recreational Activities in Schizophrenic Patients Rehabilitation in Promoting Social Skills - Masoud Fallahi-Khoshknab (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: one of group interventions in rehabilitation of schizophrenic patients is recreational activities intervention, in this type of rehabilitation therapist participates patients in recreational activities and hobbies, which promotes activity of daily livings and social skills. Our purpose of this study was investigating the effectiveness of recreational interventions in schizophrenics' social skills. Materials & Methods: in a before and after interventional study, 45 schizophrenic patients selected and assessed with Activity of Daily Living Skills Scale before intervention. Intervention was a recreational trip to MESHAD for ten days all of patients participate and work to prepare trip properties. They live, participate and work for 10 days together. Then after intervention again patients reassessed with Daily Living Skills Scale, and mean of before and after scores compared with paired T test. Results: Results showed means of score increase from 116.87 to 135.49, comparing mean of before and after means with paired T test was significant. Conclusion: recreational interventions can promote social skills in schizophrenic patients.